Pengaruh Terapi Light Message Terhadap Tekanan Darah Penderita Hipertensi Primer di Rumah Sakit Kota Batam - Rosmian Sitanggang; Mira Agusthia; Rizki Sari Utami (An-Najat, 2023)
Hypertension is a degenerative disease, blood pressure generally increases slowly with age. Hypertension therapy can be grouped into non-pharmacological and pharmacological therapy. One alternative complementary massage therapy that can be given to hypertension sufferers is light massage. The research method was an experimental method, the sample consisted of 15 respondents who underwent outpatient treatment at BP Batam Hospital with a sampling technique, namely total sampling. Data analysis used the Wilcoxon test. The research results showed that blood pressure before light massage therapy was grade I hypertension, namely 9 respondents (60%). The average blood pressure after light massage therapy was found to be that most respondents were pre-hypertensive, namely 12 respondents (80%). Bivariate analysis showed that there was a significant effect of the average blood pressure value before and after light massage therapy on the blood pressure of primary hypertension sufferers with α<0.05 (p-value= 0.001). It is hoped that the results of this research can be used as basic data for nurses in the nursing and complementary services division at Batam City Hospital to carry out activities to reduce blood pressure in hypertensive patients.